(untitled) (Global Journal of Human-Social Science, 2019)
The proper place to begin any analysis on ethnic conflicts is the partisan governance systems in which ruling elite favour some ethnic groups at the expense of others. Since the 1960s, the national executive in Kenya has had the exclusive power to grant or deny economic resources to ethnic groups that were deemed to be disloyal (Murithi, 1997). The Kenyatta Government (1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978) applied this political ideology towards the Luo Community and the Moi Government marginalised the Kikuyu community (Laaksol, 2007; CIPEV, 2008). The discriminatory allocation of resources by the executive influenced a heightened sense of ethnic consciousness among ethnic communities. Even with the return of multi-party politics, ethnic groups that perceived themselves as the out-group sought to win over state power to enable a fairer distribution of public goods and service (Alesina & Ferreira, 2004).This political culture occasioned the in-group and out-group mentality in politics and socio-and economic phenomenon.